La construcción cultural y política de la etnicidad en el Perú: José Carlos Maríategui, José María Arguedas y Rodrigo Montoya - Baptista, Selma (2005)
This article delineates the intelectual paths of some Peruvian intelectuals, specially anthropologists, stating their conceptions of nationality, national identity, ethnicity and politics, retracing historically and culturally some traditional and revolutionary trends of thought of the country. From the indigenist beginnings elaborated by Valcarcel, passing through the socialism of Mariategui, it arrives to the «magical socialism» of Jose Maria Arguedas and Rodrigo Montoya Rojas, as actual and creative interpretative possibilities of Peruvian anthropological thought.